Key drivers of the rebound trend of China’s CO2 emissions - Yaxin Zhang; Xinzhu Zheng; Wenjia Cai; Yuan Liu; Huilin Luo; Kaidi Guo; Chujie Bu; Jin Li; Can Wang (Environmental Research Letters, 2020)
China’s CO _2 emissions declined by 5.1% in 2013–2016 as China steps into a new period of development, in which the economy shifts from the previous high-speed growth driven by input and investment to a medium-speed growth driven by innovation and consumption. However, the decline did not continue; the national CO _2 emissions rebounded since 2016, with the drivers of the rebound unclear. Here, we apply the input–output structure decomposition analysis to decompose emissions in 2002–2017 to reveal driving factors of the emission rebound trend. Results show that the input–output structure among sectors (partially reflecting production structure) and the demand pattern have contributed to emission reduction as China entering ‘the new normal’ pattern of development. However, the two factors reversed and therefore induced emissions, contributing to 5.2% and 0.1% of the increase in emissions since 2015. Such obvious contribution reversal can be explained as a new round of infrastructure stimulated substantial energy consumption and the electricity demand was mainly supported by coal-fired power (59.0%). Besides, the emission reduction effect of the energy mix has shrunk from −11.8% in 2012–2015 to −6.9% in 2015–2017, closely related to the slowing growth of renewable energy and the slight recovery of coal consumption. The findings can reasonably infer novel insights into curbing the potential reversal of China’s emission trend and aligning China’s CO _2 emission trend with the goal of achieving peak emissions before 2030.